CLINICAL CASE OF BCLC STAGE B HEPATOCELLULAR CARCINOMA WITH A COMBINED TREATMENT - Zagorulko Aleksey Ivanovich; Rozyeva Makhri Rakhimovna; Chernyaev Mikhail Viktorovich (Паёми Сино)
The article presents a clinical case of successful treatment of a patient with a BCLC stage B hepatocellular carcinoma (HCC), with the initial prediction of unfavorable radical treatment results and poor outcomes. The described approach allows the achievement of better results in patients with delayed treatment of HCC diagnosed at the advanced stage of the disease. A 69-year-old patient with pain and severe weakness was admitted to the hospital, where, according to the results of instrumental examination methods, a hepatic tumor was detected, qualified as HCC T3N0M0, stage II. Given the size and location of the tumor, combined treatment was performed, including two sessions of transarterial chemoembolization (TACE) with doxorubicin, targeted therapy with lenvatinib, microwave ablation, and surgical resection of the tumor. As a result, a progressive decrease in the tumor size was achieved with its subsequent radical removal and improved quality of life. The presented clinical case has shown that specialized care of HCC patients with advanced stages of the disease may be successful, and the accumulation of relevant experience may improve the quality and effectiveness of treatment for this group of patients.